BCG turns 100: its nontraditional uses against viruses, cancer, and immunologic diseases - Singh, Alok K.; Netea, Mihai G.; Bishai, William R. (The Journal of Clinical Investigation, 2021)
First administered to a human subject as a tuberculosis (TB) vaccine on July 18, 1921, Bacillus Calmette-Guérin (BCG) has a long history of use for the prevention of TB and later the immunotherapy of bladder cancer. For TB prevention, BCG is given to infants born globally across over 180 countries and has been in use since the late 1920s. With about 352 million BCG doses procured annually and tens of billions of doses having been administered over the past century, it is estimated to be the most widely used vaccine in human history. While its roles for TB prevention and bladder cancer immunotherapy are widely appreciated, over the past century, BCG has been also studied for nontraditional purposes, which include (a) prevention of viral infections and nontuberculous mycobacterial infections, (b) cancer immunotherapy aside from bladder cancer, and (c) immunologic diseases, including multiple sclerosis, type 1 diabetes, and atopic diseases. The basis for these heterologous effects lies in the ability of BCG to alter immunologic set points via heterologous T cell immunity, as well as epigenetic and metabolomic changes in innate immune cells, a process called “trained immunity.” In this Review, we provide an overview of what is known regarding the trained immunity mechanism of heterologous protection, and we describe the current knowledge base for these nontraditional uses of BCG.